An Overview of Electronic Games in the Academic Areas - Alfarsi G.; Bin Mohd. Yusof A.; Tawafak R.M.; Iqbal Malik S.; Mathew R.; Waseem Ashfaque M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education sectors; Electronic games; Forward looking; Latent capacity; Artificial intelligence